1979
DOI: 10.3109/inf.1979.11.issue-3.02
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster in Infancy

Abstract: Three cases of herpes zoster occurring in infancy are reported. In each case the mother had chickenpox in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…3 The interval between varicella and childhood zoster averages 3.8 years if varicella occurs during the first year of life vs. 6.2 years if varicella occurs after the age of 1 year. 22 Studies of zoster in pediatric patients 1,3,21,22 did not find that childhood zoster was the harbinger of an underlying immunodeficiency, malignancy or HIV infection.…”
Section: Zoster In Pediatric Patientsmentioning
confidence: 96%
See 2 more Smart Citations
“…3 The interval between varicella and childhood zoster averages 3.8 years if varicella occurs during the first year of life vs. 6.2 years if varicella occurs after the age of 1 year. 22 Studies of zoster in pediatric patients 1,3,21,22 did not find that childhood zoster was the harbinger of an underlying immunodeficiency, malignancy or HIV infection.…”
Section: Zoster In Pediatric Patientsmentioning
confidence: 96%
“…Several studies of pediatric patients with zoster 1,3,21,22 reported that the most common risk factor for developing zoster was having had varicella before 1 year of age. This can be explained by a decreased development of cellular and humoral immunity to VZV, when varicella occurs during the first year of life.…”
Section: Zoster In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…When zoster occurs in children who have not previously had chickenpox, there is often a history of intrauterine exposure to VZV. In these reports, the mothers contracted chickenpox during gestation, but gave birth to normal infants who, without ever developing chickenpox despite frequent childhood exposure, developed typical zoster at a young age, many in the first few months of life [74,260,[295][296][297][298][299]. In most of these infants, the course of zoster was benign.…”
Section: Zoster In Neonates and Older Childrenmentioning
confidence: 98%
“…In most of these infants, the course of zoster was benign. One infant developed a second attack of zoster when 10 months old; the first occurred when the infant was 4 months old [295].…”
Section: Zoster In Neonates and Older Childrenmentioning
confidence: 99%